A Prevalence and Management Study of Acute Pain in Children Attending Emergency Departments by Ambulance. (2nd January 2016) - Murphy, Adrian; McCoy, Siobhan; O'Reilly, Kay; Fogarty, Eoin; Dietz, Jason; Crispino, Gloria; Wakai, Abel; O'Sullivan, Ronan
Abstract: Pain is the most common symptom in the emergency setting and remains one of the most challenging problems for emergency care providers, particularly in the pediatric population. The primary objective of this study was to determine the prevalence of acute pain in children attending emergency departments (EDs) in Ireland by ambulance. In addition, this study sought to describe the prehospital and initial ED management of pain in this population, with specific reference to etiology of pain, frequency of pain assessment, pain severity, and pharmacological analgesic interventions. A prospective cross-sectional study was undertaken over a 12-month period of all pediatric patients transported by emergency ambulance to four tertiary referral hospitals in Ireland. All children (<16 years) who had pain as a symptom (regardless of cause) at any stage during the prehospital phase of care were included in this study. Over the study period, 6, 371 children attended the four EDs by emergency ambulance, of which 2, 635 (41.4%, 95% confidence interval 40.2–42.3%) had pain as a documented symptom on the ambulance patient care report (PCR) form. Overall 32% ( n = 856) of children who complained of pain were subject to a formal pain assessment during the prehospital phase of care. Younger age, short transfer time to the ED, and emergency calls between midnight and 6 am were independently associated with decreased likelihood of having a documented assessment of pain intensity during the prehospital phase of care. Of the 2, 635 children who had documented pain on the ambulance PCR, 26% ( n = 689) received some form of analgesic agent prior to ED arrival. Upon ED arrival 54% ( n = 1, 422) of children had a documented pain assessment and some form of analgesic agent was administered to 50% ( n = 1, 324). Approximately 41% of children who attend EDs in Ireland by ambulance have pain documented as their primary symptom. This study suggests that the management of acute pain in children transferred by ambulance to the ED in Ireland is currently poor, with documentary evidence of only 26% receiving prehospital analgesic agents.